Using Media in Religious Studies. Strategies of Representing Religion in Scholarly Approaches Using Media in Religious Studies - Larissa Soares Carneiro (Journal for Religion, Film and Media, 2017)
Compared to the broad and well established field of research on media within religions, the usage of media for representing religion in scholarly work - text, image, sound, material, speech, film etc. - is a rather neglected topic. This is astonishing, since media have different effects and are perceived with different impacts not only in religions but also inside the scientific community. This shapes our perception and needs to be separated from processes of understanding media within religions. The issue explores media as a crucial part of research, as means for both producing and representing scholarly results. This issue of JRFM focuses mainly two topics: didactics of teaching religious studies and exhibiting religions. An example like the Qur'an illustrates the complexity and connectivity of media and their representations. As the Qur'an might occur as script, print, sound or in the internet, it induces scholars first to use adequate forms to mediate emic habitual practices of reading, touching and reciting, and second to choose forms that are useful for etic reflections on emic perceptions. The emic and etic perception might differ especially when media do not only transport narratives or any religious knowledge but represent an idea of transcendence and evoke elementary religious feelings. Exhibitions, as another example, are results of complex processes to transfer historical or empirical knowledge via selected materials to the sensual perception of visitors. But this transfer is not only a part of scholarly exhibitions but also occurs when museums become missionary tools. Media are in any case not only signs and symbols to communicate or transport knowledge, but they are part of worldviews, emotional and habitual sets of sensation, which, interestingly enough, reveal religions and scholarly approaches as overlapping. Therefore, a specific reflection on our perspectives and insights into recipients' possible perceptions are necessary if our aim is to inform and make our own methods transparent and suitable to what we want to express. This issue wants to stimulate further methodological reflections on this field. As usual book reviews as well as two calls for papers for upcoming issues of JRFM complete the volume.